Motivating factors, potential deterrents and perceived physical impacts of blood donation on donors - Elizabeth Joseph, Serena; Mary Bose, Binu; Joseph, Elizabeth; Poothiode, Usha (Tropical Journal of Pathology and Microbiology, 2019)
Background: Blood is a vital component of the human body, which constitute 7% of the body weight. To ensure an adequate supply of blood, it is necessary to make significant improvements in methods for recruiting and retaining donors and to increase their efficiency. This study was done to understand the factors that motivate and deter donors and also to assess the physical impacts perceived after blood donation. Materials and methods: A descriptive, cross-sectional study was conducted among voluntary donors coming to a blood bank using a self-administered questionnaire. The questionnaire contained sections pertaining to motivating factors, potential deterrents and perceived physical impacts of blood donation. Statistical analysis was performed using R-software. Results: The total number of donors was 113 out which of female donors comprise 5.3% and male donors 94.7%. Altruism (73.1%) and pain due to phlebotomy (8.8%) was the strongest motivating and deterring factor respectively. Positive effects were perceived more than negative effects. Peer influence has a significant association with the level of education of the donors (X2 test was performed and p=0.03). As far as the occupation was considered availing leave was not a significant motivating factor (p<0.015). Social media hasn’t significantly influenced the donors in considering their occupation and place of residence (p<0.0009, p<0.0027). Conclusion: From the present study it can be inferred that the present awareness regarding blood donation through social media is inadequate. Thus, increased focus should be given on improving the awareness through social media.